Suspected urolithiasis in a female zoo yak (Bos grunniens) based on urolith analysis - R. Mihaylov; V. Gerzilov; D. Kanakov; Zh. Zheleva; B. Mihaylov (Bulgarian Journal of Veterinary Medicine)
Numerous publications devoted to urolithiasis in domestic animals are encountered in the scientific literature. Although less frequently, there are reports on urolithiasis occurrence in wild animals, living either freely in nature or in captivity. Uroliths may form in the urinary tract both of male and female mammals with equal prevalence, yet the clinical disease associated with obstruction or partial ob-struction of urinary ducts is much more common in male animals. This is the most probable reason for the lack of scientific reports of spontaneously excreted uroliths in the literature. An accidental finding of four uroliths within a cage facility on the territory of the Stara Zagora Zoo was the incen-tive for their macroscopic and stereoscopic analysis, as well as powder X-ray diffraction (XRD) anal-ysis of the phase composition of the samples. The stones were identified as struvite, composed of magnesium ammonium phosphate (MgNH4PO4.6H2O). Our hypothesis was that they were excreted by a female yak (Bos grunniens) reared in the facility because of their size and some specific biological features of yaks.